2018
DOI: 10.1016/j.jbo.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast suppression in multiple myeloma bone disease

Abstract: Multiple myeloma (MM) is the most frequent cancer to involve the skeleton with patients developing osteolytic bone lesions due to hyperactivation of osteoclasts and suppression of BMSCs differentiation into functional osteoblasts. Although new therapies for MM have greatly improved survival, MM remains incurable for most patients. Despite the major advances in current anti-MM and anti-resorptive treatments that can significantly improve osteolytic bone lysis, many bone lesions can persist even after therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 87 publications
(148 reference statements)
0
33
0
Order By: Relevance
“…MM is characterized by bone osteolytic lesions that result from an imbalance between osteoclastic and osteoblastic compartments [4,26]. Osteoblastic activity is downregulated in MM [16,27]. MM cells inhibit the differentiation of MSCs into osteoblasts by especially producing the Wnt inhibitor DKK1 [5,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MM is characterized by bone osteolytic lesions that result from an imbalance between osteoclastic and osteoblastic compartments [4,26]. Osteoblastic activity is downregulated in MM [16,27]. MM cells inhibit the differentiation of MSCs into osteoblasts by especially producing the Wnt inhibitor DKK1 [5,28].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we and others have demonstrated that MSCs are abnormal in MM [12][13][14]; in particular, they produce not only excess MM growth factors such as interleukin-6 (IL-6) [15] but also growth and differentiation factor 15 (GDF15), which is also responsible for chemoprotection [8]. Importantly, their ability to differentiate in osteoblasts is severely impaired, even without any contact with MM cells [16], one explanation being their abnormally high secretion of the Wnt inhibitor Dickkopf 1 (DKK1).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is quite understandable why most of the drugs in the market for bone metastatic patients are bone targeted. An interesting proposition about harnessing osteoblasts, based on data from patients, in vivo experiments, and co cultures, suggest that osteoblasts and their secretomes were hostile to growth of myeloma cells in the bone (124,125). Similar in vitro data in the case of breast cancer also showed that introduction of osteoblasts curbed bone turnover caused by osteolytic breast cancer (126).…”
Section: Therapeutic Perspectivementioning
confidence: 99%
“…Increased bone resorption releases bone matrix–embedded growth factors such as transforming growth factor beta (TGF‐β), which further stimulates tumor growth and bone destruction . Concomitantly, cancer cells secrete factors (interleukin [IL]‐7, IL‐3, Dickkopf Wnt Signaling Pathway Inhibitor 1 [DKK‐1], and Sclerostin) and promote epigenetic changes that suppress osteoblast differentiation and function (reviewed in Giuliani and colleagues, (28) MacDonald and Delgado‐Calle, and Adamik and colleagues). As a result, bone is resorbed at a rate faster than it is formed, causing the development of overt “osteolytic lesions,” which severely weakens the bone and elevates fracture risk.…”
Section: Introductionmentioning
confidence: 99%